2017
DOI: 10.1111/resp.12976
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant of MAP2K7 is associated with increased risk of COPD in southern and eastern Chinese

Abstract: Our data strongly suggest that the p.Glu116Lys rare variant in MAP2K7 predisposes its carriers to develop COPD, which would provide a useful genetic biomarker for COPD susceptibility in Chinese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…22 Although cigarette smoking is the most significant risk factor, only a fraction of smokers develop COPD, so genetic associations should also be considered when assessing potential risk factors. Qiu et al 23 found that rare variants (Glu116Lys) in mitogen-activated protein kinase 7 (MAP2K7) in southern and eastern Chinese were associated with elevated risk of COPD. Epigenetic regulation of gene expression was also shown to be modified in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…22 Although cigarette smoking is the most significant risk factor, only a fraction of smokers develop COPD, so genetic associations should also be considered when assessing potential risk factors. Qiu et al 23 found that rare variants (Glu116Lys) in mitogen-activated protein kinase 7 (MAP2K7) in southern and eastern Chinese were associated with elevated risk of COPD. Epigenetic regulation of gene expression was also shown to be modified in COPD.…”
Section: Introductionmentioning
confidence: 99%